Chicken liver morphology as affected by feed withdrawal time and dietary aflatoxins. Issue 4 (4th July 2022) - François, E.; Vieira, S. L.; Kindlein, L.; Bess, F.; Xavier, B.; Soster, P.; Stefanello, C.
ABSTRACT: 1. An investigation was conducted on the effects of aflatoxin (AFL)-contaminated diets and feed withdrawal periods from 0 to 12 h in broiler chickens at 28 d of age. Both factors can potentially affect liver colour and can cause failure at veterinary inspection in the slaughterhouse. 2. A total of 240, one-d-old female Cobb 500 broiler chickens were fed a common corn-soy pre-starters (d 1–7) and then either a non-contaminated control (CON) or feed with 1 ppm AFL (AFL) from d 8 to 28. The inoculum of AFL had 792 ppb of aflatoxin B1, 35 ppb of aflatoxin B2 and 219 ppb of aflatoxin G1. On d 28, all broilers were weighed and euthanised for necropsy following three different feed withdrawal time periods (0, 6 or 12 h), in a 2 × 3 factorial arrangement. 3. Body weight gain, liver weight and liver fat content decreased as feed withdrawal lengthened, whereas FCR and gallbladder weight increased ( P ≤ 0.05). AFL-fed birds had reduced body weight and proportion of liver fat and increased FCR, liver and gallbladder weights ( P ≤ 0.05). 4. Livers from fed broilers (0 h withdrawal) showed more lightness (L*) and yellowness (b*) than livers of broilers from 6 or 12 h withdrawal ( P ≤ 0.05). The L* and redness (a*) values of livers from broilers fed diets COB were lower than those from AFL fed broilers ( P ≤ 0.05). 5. Prolonging pre-slaughter feed withdrawal decreased liver L*, whereas feeding AFL increased liver b*. These findings can be used to support veterinary assessment in slaughterhouses as shackled birds move on line through the inspection site. Since chicken liver is a valuable organ and an indicator of animal health, attention must be paid to these differences to ensure consumer safety.